2008
DOI: 10.1016/j.jcrs.2008.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure on the first postoperative day as a prognostic indicator in phacoemulsification combined with deep sclerectomy

Abstract: An IOP of 9 mm Hg or less on the first postoperative day might serve as a positive prognostic indicator in combined phacoemulsification with deep sclerectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Day 1 IOP appears to be a significant prognostic factor in combined PKE + NPDS surgery, as shown by Garcia-Pérez et al Day 1 IOP < 9 mmHg was associated with a higher success rate and fewer treatments and goniopunctures [17]. In the present study we had similar results with a complete success rate significantly higher in the subgroup of patients undergoing PKE + NPDS with an IOP < 9 mmHg at Day 1 (p = .02).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Day 1 IOP appears to be a significant prognostic factor in combined PKE + NPDS surgery, as shown by Garcia-Pérez et al Day 1 IOP < 9 mmHg was associated with a higher success rate and fewer treatments and goniopunctures [17]. In the present study we had similar results with a complete success rate significantly higher in the subgroup of patients undergoing PKE + NPDS with an IOP < 9 mmHg at Day 1 (p = .02).…”
Section: Discussionsupporting
confidence: 87%
“…However, this was not observed for the PKE + XEN procedure in our study. In NPDS, IOP at Day 1 is an indicator of adequate inner scleral flap dissection and juxtacanalicular trabecular meshwork removal [17], which provides a better result. Although XEN implant provides constant resistance with a steady-state pressure of approximately 6-8 mmHg following an uncomplicated implantation under normal physiologic conditions and without conjunctival resistance to the outflow [9], Day 1 IOP does not seem to be a predictor of long-term outcomes for the XEN, whether it was a standalone or a combined procedure [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Deep sclerectomy (DS) is a nonpenetrating glaucoma surgery (NPGS) technique that has been demonstrated to be as effective as TRAB, but may be less affected by significant postoperative complications. 3 It has been extensively reported that the success rate of DS may be enhanced by the intraoperative use of implants, 4,5 such as purified porcine collagen (Aquaflow), 6,7 reticulated hyaluronic acid (SK-GEL), 8,9 acrylic material (T-Flux), 10 and injectable crosslinked hyaluronic acid (Healaflow; Anteis, Geneva, Switzerland). 11 Intraoperative cross-linked hyaluronic acid was proven to reduce postoperative scarring and adhesions, 12 and to improve the outcome of DS as well as other glaucoma surgical procedures (ie, drainage implants).…”
mentioning
confidence: 99%
“…Nonpenetrating deep sclerectomy long-term IOP control [29,135]. Usually, the IOP builds up within a few days to the level of 8-10 mmHg and, in most cases, the AC remains deep.…”
Section: Reviewmentioning
confidence: 99%